Some Reflections on "The Nature and Significance of Economics" - Parsons, Talcott (Quarterly Journal of Economics, 1934)
I. Professor Robbins' tendency to “Radical Positivism” — The incompatibility of the means-end schema with the ideal of economics as a “positive” science in this sense, 512. — Criticism of his “atomism,” 516. — II. Outline of the general chain of means-ends relationships as a schema for classification of the sciences of action, 521. — The place of the “economic” element, 522. — Critical application to Professor Souter's position, 529. — His empiricist tendency and its implications, 534. — III. Some special problems: “Formalism,” 536. — Economic law and the realm of the “irrational,” 538. — Precision, Dynamics, 540. — Conclusion, 543.